Enigmatic role of auxin response factors in plant growth and stress tolerance - Liu, Ling; Yahaya, Baba Salifu; Li, Jing; Wu, Fengkai (Frontiers in Plant Science, 2024)
Abiotic and biotic stresses globally constrain plant growth and impede thelimit plant growth worldwide and hinders optimization of crop productivity. The phytohormone auxin is involved in nearly everyhas been implicated in almost all aspects of plant development. Auxin acts as a chemical messenger that influences gene expression through a short nuclear pathway, mediated by a family of specificdistinct DNA-binding transcription factors known as AUXIN RESPONSE FACTORS (ARFs) transcription factors. ARFs thus act as effectors of auxin response and translate chemical signals into the regulation of auxin responsive genes. Since the initial discovery of the first ARF in Arabidopsis, advancementsprogress in genetics, biochemistry, genomics, and structural biology have facilitatedhas led to the development of models elucidatingexplaining ARF action and their contributions torole in generating specific auxin responses. Yet, significant gaps persist in our understanding ofHowever, much remains unknown about ARF transcription factors despite these endeavorsefforts.UnravelingUnderstanding the functional roles of ARFs in regulating stress response regulation, alongside elucidatingalong with their genetic and molecular mechanisms, is still in its nascent phaseearly stages. Here, we review recent research outcomes on ARFs, detailing their involvement in regulating and summarize its role in the regulation of leaf, flower, and root organogenesis and development, as well as, stress responses and their corresponding associated regulatory mechanisms: including gene expression patterns, functional characterization, transcriptional, post-transcriptional and post-translationaltranscriptional regulation acrossunder diversevarious stress conditions. Furthermore, We we delineate unresolvedfurther identify outline outstanding questions and forthcoming challenges infor the near future with regards to ARF research.